Reliability and objectivity of the susceptibility test of the body injuries during a fall of physiotherapy students - Jarosław Klimczak; Michał Oleksy; Bartłomiej Gąsienica-Walczak (Physical Education of Students, 2022)
Background and Study Aim. Falling is an increasingly frequent problem. Assessment of the ability to control the body parts that are most susceptible to injury during a fall is the primary goal of prevention of fall-related injuries. The susceptibility test of the body injuries during a fall (STBIDF) is of note. To date, investigations of the STBIDF have been limited to validity assessment. Aim. Verify the reliability and objectivity of the STBIDF test.